Peran Pusat Informasi Dan Konseling (PIK-KRR) Terhadap Perilaku Seksual Berisiko Pada Smpn Terpilih Di Jakarta Selatan Tahun 2016 - Putri Andriani (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2016)
Sexuality among teenagers needs to be directed seriusly into behavior that does not bring any risks. One of the intervention given to adolescent reproductive health concerning sexuality is by providing reproductive education to schools. This was a comparative study using a cross sectional method in two junior high school which had and did not have the Information and Counseling Center of Reproductive Health (PIK-KRR) amounted to 136 samples. Data was analyzed with Mann Whitney test. This research showed that there was a significant difference in attitute in risky sexual behaviour (p=0.000) and knowledge level of health reproduction (p=0.000) between school which had and did not have PIK-KRR. In bivariate analysis, there was a significant difference in gender to risky sexual activity, porn media access to risky sexual activity, gender to attitude of risky sexual behaviour, religiousity to attitude, attitude to porn media access, attitude to peer affect (p=0.004) and religiousity to knowledge level of health reproduction. This study concluded that the level of knowledge had a significant relationship with risky sexual behavior among adolescents at the two study sites.